Individual Conditions of Journalistic Production in Cuban Independent Media - Somohano Fernández, Abel (2022)
This paper analyzes the individual conditions of journalistic production in two independent medias of the media-partisan structure in Cuba. These can be considered among the most internationally recognized Cuban media. In the research, in-depth interviews with 40 journalists. It was found that these conditions are marked, fundamentally, by the confluence in the two media organizations of young graduates of journalism courses in the country with a multiple spatial location, and different referents and professional trajectories. A professional identification with the functions of journalism to inform, monitor power, participate in social debate and show society in its diversity, among others, was also detected. In addition, personal concerns were found about the violence against independent journalism on the island. It was concluded that these conditions materialize in terms of an anti-authoritarian professional discursiveness (and representation) shared by journalists. A comparison with the findings of inquiries located in other national spaces is proposed in the conclusions.